Phenomenal causality and response to frustrating interpersonal events - Rodrigues, Arnoldo; Das Vitorias Jouval, Maria (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An experiment was carried out to test the following 3 hypotheses: (1 ) in any frustrating interpersonal relation, the affective bond between the frustrating and the frustrated person will determine the latter’s attributions. There will be more attribution of personal causality when the interpersonal relation is negative than when it is positive; (2) any frustrating interpersonal event always leads to anger in the frustrated person; (3) aggressive reactions will only occur when the frustrated person attributes personal causality to the frustrating agent.